Determinación del índice de prevalencia del balantidium coli en cerdos de la ciudad de Machala - Chávez Orellana, Andrea Beatriz (2014)
This research was conducted in the city of Machala Provincia de el Oro, during the months of February through May 2014. The objectives were. To determine the Prevalence Index Balantidium coli in pigs in the city of Machala. To determine the prevalence rate of Balantidium coli by race and age.The numbers of samples were 150 animals.Universe: It consists of four pig farms.Sample: It consists of piglets from birth to 6 months of age.The methodology used was to fill the control sheet with the owner, and then make the collection of samples directly from the anus of the pigs or collected from the ground, as long as the samples are recent, although the approximately 5g sample of feces will be chosen from the inside. Later to be transferred to the parasitology laboratory of the Universidad Técnica de Machala, Facultad de Ciencias Agropecuarias.In this investigation the presence of Balantidium coli in pigs in the city of Machala, with 51 of the 150 positive animals sampled representing 34% was determined.